The Politics of food [videorecording] a question of aid (Yorkshire Televisions, 1988)
Summary: Presents the Kerala and Bangladesh government programs to ensure high standards of health, education, birth control and nutrition. In Kerala, food is equally shared and every person can afford basic nutrition while Bangladesh is heavily dependent on foreign aid, most of which is used to support the rural middle class, and so the rural poor remained malnourished and uneducated.